Peacebuilding and international administration : the cases of Bosnia and Herzegovina and Kosovo - Van Willigen, Niels (Milton Park, Abingdon, Oxon : Routledge, 2013)
'This book provides a detailed historical and political analysis of the role and effectiveness of international administration in state-building. It analyses how the international administrations in Bosnia and Herzegovina and Kosovo have attempted to create sustainable political institutions and to what extent they have been successful in doing so'--
1. Introduction -- 2. International administration -- 3. The cases of Bosnia and Kosovo -- 4. Institutional autonomy -- 5. Institutional congruence -- 6. Institutional support -- 7. Conflict resolution attempts -- 8. Conclusion.
Includes bibliographical references (p. [198]-218) and index.
Mode of access: World Wide Web.
Keywords: International agencies -- Bosnia and Hercegovina -- Politics and government; International agencies -- Kosovo (Republic); Bosnia and Hercegovina -- Politics and government; Kosovo (Republic) -- Politics and government; Electronic books